Emotional and behavioural problems of left behind children in Lithuania: a comparative analysis of youth self-reports and parent/caregiver reports using ASEBA - Račaitė, Justina; Antia, Khatia; Winkler, Volker; Lesinskienė, Sigita; Sketerskienė, Rita; Maceinaitė, Rūta; Tracevskytė, Ingrida; Dambrauskaitė, Elena; Šurkienė, Genė (Child and adolescent psychiatry and mental health, 2024)
Children being left behind (LBC) in their home countries due to parental emigration is a global issue. Research shows that parents’ emigration negatively affects children’s mental health and well-being. Despite a high number of LBC, there is a dearth of data from Eastern European countries. The present study aims to collect and analyse self-reported data on LBC emotional and behavioural problems and compare children’s reports with those of parents/caregivers.